THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, SERVANT LEADERSHIP, PERCEIVED ORGANIZATIONAL SUPPORT AND JOB SATISFACTION TO LIFE SATISFACTION - Erwin Santosa; Yohana Palupi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Research of effect transformational, perceived organizational support and jobsatisfaction to life satisfaction by Erwin used pandemic Covid 19 as aphenomenon to bring up this article surface. COVID-19 pandemic has beengoing for more than a year since March 2020 when Indonesia governmentofficially announced the first case of this corona virus. COVID-19 pandemicitself had a significant impact in a lot of sectors from socio-cultural, economic and political then requires new adaptation efforts that constantly beingcarried out by organizations in Indonesia. The organizations stopped allactivities since March 22, 2020 where the government issued a Circular Letterfrom the Ministry of Health on March 16, 2020 and began to continuous makechanges from a physical into a digital. Using quantitative method to testingthe path analysis with several indicators measurement completed with Likertscale to find the result. A hundred respondents are invited for this research.The result shown transformational leadership has positive and significantimpact to perceived support organizational, job satisfaction and lifesatisfaction. Perceived support organization has positive and significantimpact to job satisfaction and life satisfaction. Thus, job satisfaction also haspositive and significant impact to life satisfaction